2015
DOI: 10.1590/2317-1782/20152014139
|View full text |Cite
|
Sign up to set email alerts
|

Perception of hearing protectors by workers that participate in hearing preservation programs: a preliminary study

Abstract: PURPOSE: To evaluate and compare the workers' perception of comfort and use aspects regarding two types of hearing protectors (shell and earplug), in three units from a lumbering company, with different implantation times for Hearing Preservation Programs.METHODS: This is a cross-sectional study comparing 440 workers' perception of hearing protectors, from three companies in Paraná State (Brazil), with different times for Hearing Preservation Programs. Two closed questionnaires were applied (9 and 10 questions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
3

Year Published

2018
2018
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 17 publications
0
18
0
3
Order By: Relevance
“…Only few studies consider the HPD comfort in a more holistic perspective (Arezes, Abelenda, and Braga 2008;Brown-Rothwell 1986;Gonçalves et al 2015;Hsu et al 2004;Lhuede 1980). Hsu et al (2004) consider acoustical and non-acoustical comfort attributes such as: "having difficulties in conversation", "feeling itchy", "acoustic change", "interfere with work", "discomfort due to hard contact part".…”
Section: Concepts and Constructs Found In The Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Only few studies consider the HPD comfort in a more holistic perspective (Arezes, Abelenda, and Braga 2008;Brown-Rothwell 1986;Gonçalves et al 2015;Hsu et al 2004;Lhuede 1980). Hsu et al (2004) consider acoustical and non-acoustical comfort attributes such as: "having difficulties in conversation", "feeling itchy", "acoustic change", "interfere with work", "discomfort due to hard contact part".…”
Section: Concepts and Constructs Found In The Literaturementioning
confidence: 99%
“…The second group of questionnaires is distributed during or after the wearing of the tested HPD to evaluate the attributes of perceived comfort and/or the HPD design factors that might influence the perceived comfort. These questionnaires usually measure the HPD wearer's opinions/feelings through rating scales such as unipolar Likert-type scales (Brown-Rothwell 1986;Du, Homma, and Saunders 2008;Hsu et al 2004), bipolar scales (Behar and Desormeaux 1986;Casali et al 1987;Epps and Casali 1985;Park and Casali 1991) or both (Sweetland 1983;Gonçalves et al 2015). Even if it is based on a restricted construct of comfort, a questionnaire developed by Park and Casali (1991;1992) generates consensus and is used as is or slightly modified in many studies (Arezes and Miguel 2001;Arezes and Miguel 2002;Byrne et al 2011;Davis et al 2011;Davis and Shaw 2016;Samelli et al 2018;Sviech et al 2013).…”
Section: Questionnairesmentioning
confidence: 99%
“…Diversos fatores dificultam a utilização eficiente de protetores auriculares, a começar pelos níveis de ruído muito intensos que não são possíveis de serem atenuados unicamente pelos protetores auriculares 46 . Além disso, fatores como as técnicas de colocação dos protetores auriculares, o conforto, a aceitação do usuário, o custo e a durabilidade desses equipamentos, problemas de comunicação, segurança e higiene, entre outros, interferem na utilização eficaz dos protetores auriculares 3,47 .…”
Section: Discussionunclassified
“…Além dos efeitos nocivos do ruído intenso sobre a audição, há prejuízo também aos sistemas circulatório, endócrino, digestivo e neurológico, além da contribuição para o aumento do número de acidentes de trabalho; o processo de comunicação é afetado como um todo quando há a PAIR, o que também leva à deterioração da qualidade de vida do trabalhador 3 .…”
Section: Introductionunclassified
“…A similar result was found by the authors when they evaluated and compared the perception of 440 workers from a logging company in municipalities from the interior of Paraná State, Brazil. They concluded that the most relevant aspects considered for the use of the equipment were noise reduction by the protector and verbal communication 31 .…”
Section: Discussionmentioning
confidence: 99%